OPTIMASI RUTE TRUK PENGANGKUTAN SAMPAH DI KOTA SUMBAWA BESAR SHIFT II MENGGUNAKAN GVRP - Koko Hermanto; Eki Ruskartina (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2018)
The problem of garbage in the city of Sumbawa Besar is a common problem that often occurs, as well as large cities in Indonesia. To avoid the negative impact of the existence of waste, the waste problem needs to be handled properly by improving quality and waste management, for example in terms of distribution. Set warehouse, TPS and TPA as vertices, and the connecting paths of these vertices are edgy. Arrange the shortest route for each fleet in the second shift using the generalized vehicle routing problem (GVRP) method. Then, using the clustered generalized vehicle routing problem (CGVRP) method and resolved with the Dijkstra algorithm. Obtained the total route on the second shift 85,569 meters, so that spent fuel RP 69,524, - more optimal than the route that has been used that is along 96,302 meters obtained RP. 78,245, -.